2012
DOI: 10.1590/s0100-879x2012007500026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis of chronic atrophic gastritis: changes of protein expression in chronic atrophic gastritis without Helicobacter pylori infection

Abstract: Chronic atrophic gastritis (CAG) is a very common gastritis and one of the major precursor lesions of gastric cancer, one of the most common cancers worldwide. The molecular mechanism underlying CAG is unclear, but its elucidation is essential for the prevention and early detection of gastric cancer and appropriate intervention. A combination of two-dimensional gel electrophoresis and mass spectrometry was used in the present study to analyze the differentially expressed proteins. Samples from 21 patients (9 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…15, 3 2013 Введение Считается, что развитие аденокарцином же-лудка представляет взаимосвязанные между со-бой патогенетические звенья (каскад Correa): поверхностный (неатрофический) гастрит -атрофический гастрит -кишечная метапла-зия -дисплазия -рак [7], поэтому хронический атрофический гастрит (ХАГ), являющийся рас-пространенным заболеванием желудочно-ки-шечного тракта, относят к предраковым состо-яниям желудка [26,29]. ХАГ характеризуется, помимо атрофии, воспалительными изменени-ями в слизистой оболочке желудка (СОЖ) [2], которые сопровождаются продолжительной ста-дией регенерации в условиях длительно сохра-няющейся гипоксии и активации внеклеточного протеолиза с ускорением процесса мобилизации и деления незрелых эпителиальных клеток, с бло-кированием их созревания и увеличением гене-тической нестабильности с нарастанием числа мутаций [3,25].…”
Section: цитокины при атрофическом гастритеunclassified
“…15, 3 2013 Введение Считается, что развитие аденокарцином же-лудка представляет взаимосвязанные между со-бой патогенетические звенья (каскад Correa): поверхностный (неатрофический) гастрит -атрофический гастрит -кишечная метапла-зия -дисплазия -рак [7], поэтому хронический атрофический гастрит (ХАГ), являющийся рас-пространенным заболеванием желудочно-ки-шечного тракта, относят к предраковым состо-яниям желудка [26,29]. ХАГ характеризуется, помимо атрофии, воспалительными изменени-ями в слизистой оболочке желудка (СОЖ) [2], которые сопровождаются продолжительной ста-дией регенерации в условиях длительно сохра-няющейся гипоксии и активации внеклеточного протеолиза с ускорением процесса мобилизации и деления незрелых эпителиальных клеток, с бло-кированием их созревания и увеличением гене-тической нестабильности с нарастанием числа мутаций [3,25].…”
Section: цитокины при атрофическом гастритеunclassified
“…It is widely accepted that gastric carcinogenesis is a continuous process starting from non‐atrophic gastritis to chronic atrophic gastritis (CAG; i.e. loss of specialized glands), to metaplasia and dysplasia, and finally to adenocarcinoma (Zhang, Hou, Wu, & Li, 2012). Reducing the risk of gastric cancer by improving CAG in patients is seen as a significant treatment option (Xu, Qin, & Liu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that patients with CAG had the lower serum PGR than those without CAG, and the optimal PGR cut-off values for predicting CAG of the antrum and of the corpus were 4.9 and 3.5, respectively [30] . One comparative proteomics analysis showed that up-regulation of ribosomal protein S12 (RPS12) and down-regulation of proteasome activator subunit 1 (PSME1) were involved in the development of CAG [31] . Another analysis of genomic expression profiles found that five genes were associated with H. pylori-related CAG, including ATP6V0B, ATP6V1G1, ATP6V1F, NDUFV2 and NDUFS5 [32] .…”
Section: Introduction O F M O L E C U L a R Pathological Ementioning
confidence: 99%